Arsenic exposure and seafood intake in Korean adults. (May 2017) - Bae, H-S; Kang, I-G; Lee, S-G; Eom, S-Y; Kim, Y-D; Oh, S-Y; Kwon, H-J; Park, K-S; Kim, H; Choi, B-S; Yu, I-J; Park, JD
Arsenic (As) is widely distributed in the environment, and humans can be exposed to As from various sources such as air, water, soil, and food. This study was performed to evaluate the As exposure levels in Korean adults by measuring total As in urine and its relation with the consumption of seafood, a favorite food in Korea. A total of 2077 adults were the study subjects; they ranged in age from 19 to 83, and they were recruited by probability sampling stratified by area, sex, and age. None of the subjects had been exposed to As occupationally. We collected information about the demographic characteristics, lifestyles, and food consumption of study subjects using a questionnaire and followed urine sampling. Diet was assessed in individual interviews using the 24-h recall method. Total As in urine was analyzed using inductively coupled plasma mass spectrometry (PerkinElmer NEXION 300S; Concord, Ontario, Canada). The geometric mean concentration of total As in urine was observed to be 97.6 µg/L and was higher in males (103.9 µg/L) than in females (93.0 µg/L). Total As levels in urine were affected by sex, age, seafood intake, and geographic location. In this study, total As in urine was positively correlated with fish and shellfish consumption, and was mainly determined by As intake through fish and shellfish/grains/flavors. These findings suggest that seafood consumption might be a major contributor to urinary As levels in Korean adults.